2021
DOI: 10.3390/cancers13246181
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Synergy of Small Molecule Inhibitors Targeting FLT3-ITD+ Acute Myeloid Leukemia

Abstract: Constitutive activation of FLT3 by ITD mutations is one of the most common genetic aberrations in AML, present in ~1/3 of cases. Patients harboring FLT3-ITD display worse clinical outcomes. The integration and advancement of FLT3 TKI in AML treatment provided significant therapeutic improvement. However, due to the emergence of resistance mechanisms, FLT3-ITD+ AML remains a clinical challenge. We performed an unbiased drug screen to identify 18 compounds as particularly efficacious against FLT3-ITD+ AML. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bregante et al identified 2 out of 18 compounds active against FLT3-ITD AML, WS6 and Ispinesib, and combined them with two approved drugs, Ponatinib and Cabozantinib, in in vitro models (AML cell lines and samples) [ 73 ]. WS6 had a similar mechanism and potency to Ponatinib and Cabozantinib.…”
Section: Flt3i: Indications Mechanisms Of Resistance In Vitro and In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bregante et al identified 2 out of 18 compounds active against FLT3-ITD AML, WS6 and Ispinesib, and combined them with two approved drugs, Ponatinib and Cabozantinib, in in vitro models (AML cell lines and samples) [ 73 ]. WS6 had a similar mechanism and potency to Ponatinib and Cabozantinib.…”
Section: Flt3i: Indications Mechanisms Of Resistance In Vitro and In ...mentioning
confidence: 99%
“…The R/R setting still remains an unmet medical need, because of the high relapse rate observed even after HSCT. In the future, new combinations of FLT3i with inhibitors of JAK2, MEK2, HDAC, Menin, AXL and MDM2 or with multitarget agents here reported [ 73 , 74 , 76 , 77 , 78 , 79 , 81 , 82 , 83 , 87 , 91 , 93 , 94 , 95 , 97 ] and immunotherapies, such as checkpoint inhibitors, vaccines, and adoptive T-cell therapies, may decrease the burden of residual disease and reduce the incidence of relapse and refractoriness.…”
Section: Flt3i: the Past The Present The Futurementioning
confidence: 99%